Growth Mechanism of Hollow Sodium Chloride Single Crystals Grown from a Mixed Solvent of Cyclohexane and Acetone. Issue 7 (8th June 2017) - Kaneko, Shiro; Hirasawa, Izumi
Abstract: Recently, hollow sodium chloride crystals have been proposed as potential high‐value‐added crystals. The crystal growth mechanism of such crystals is elucidated using X‐ray diffraction (XRD), optical microscopic imaging, and analysis of both the chloride ions and water content in the mixed solvent of cyclohexane and acetone. A series of experimental conditions, including the stirring time after injecting the aqueous sodium chloride solutions into the mixed solvent and the ratio of cyclohexane and acetone, are evaluated in detail. Based on experimental data, possible growth mechanisms are proposed to explain the formation of hollow sodium chloride crystals. Abstract : Hollow sodium chloride crystals are considered as potential high‐value‐added crystals. Such crystals were successfully synthesized by dropping an aqueous sodium chloride solution into a mixed solvent of cyclohexane and acetone and characterized by X‐ray diffraction and optical microscopic imaging. Possible growth mechanisms were proposed to elucidate the formation of the obtained crystals.